2020
DOI: 10.1111/papt.12310
|View full text |Cite
|
Sign up to set email alerts
|

Group teletherapy for first‐episode psychosis: Piloting its integration with coordinated specialty care during the COVID‐19 pandemic

Abstract: Digital health has emerged in recent years as a tool to optimize care delivery and promote treatment adherence among individuals with first-episode psychosis (FEP). Recent mandates for social distancing and sheltering in place due to the COVID-19 pandemic have catapulted efforts to provide ongoing coordinated specialty care (CSC) on virtual platforms. While prior evidence provides support for the general implementation of virtual individual therapy, there is limited guidance and evidence for the adoption of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Literature about group teletherapy for youth with FEP during the COVID‐19 pandemic is scarce. Results of a pilot study highlight group teletherapy's advantages, as an effective, accessible and recovery‐oriented treatment approach (Wood et al, 2021 ). Furthermore, the virtual format could also allow to bring together patients and clinicians of different clinics, which could potentially greatly expand access for individuals in underserved rural areas (Wood et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature about group teletherapy for youth with FEP during the COVID‐19 pandemic is scarce. Results of a pilot study highlight group teletherapy's advantages, as an effective, accessible and recovery‐oriented treatment approach (Wood et al, 2021 ). Furthermore, the virtual format could also allow to bring together patients and clinicians of different clinics, which could potentially greatly expand access for individuals in underserved rural areas (Wood et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To foster resilience during the pandemic, ACT based interventions that emphasize values-based living can be provided remotely and offered via digital applications (Alexopoulos et al, 2020). A group-based teletherapy ACT intervention for individuals with first episode psychosis conducted during the pandemic indicated that this model was feasible to move to the virtual environment and when conducted online was acceptable to the participants, who desired more contact (Wood et al, 2021).…”
Section: Resilience Intervention Frameworkmentioning
confidence: 99%
“…Instead, participants conveyed a desire for activities to be delivered face‐face or as a combination of online and face‐face, dependent on the type of activity. Studies regarding preferences for online versus face‐face group intervention are limited, and those that exist vary in their conclusions, with some reporting that online delivery has the potential to become a standard treatment modality (Wood et al, 2021 ) and others reporting that it is worth considering ways that online groups can be incorporated into current service models (Lal et al, 2020 ). Findings from the current study suggests that further consideration around the integration of online groups and face‐face groups will be useful.…”
Section: Discussionmentioning
confidence: 99%
“…This move was supported by evidence from a systematic review that has indicated that video teleconference groups are feasible and produce outcomes similar to in‐person treatment, with high participant satisfaction (Gentry et al, 2019 ). Preliminary evidence from Wood et al ( 2021 ) concluded that implementing online group therapy for individuals with first‐episode psychosis (FEP) during the COVID‐19 pandemic had the potential to become a standard treatment modality for clients receiving specialty care for FEP. While online, telehealth delivered group interventions had not been previously used at Orygen, this existing research and the context of the COVID‐19 pandemic enabled the rapid move to this mode of delivery and to proactively evaluate the provision of these services.…”
Section: Introductionmentioning
confidence: 99%